Philanthropy in Education: Diverse Perspectives and Global Trends - Arushi Terway (NORRAG Series on International Education and Development, 2019)
Challenging commonly held perceptions of philanthropic organisations, this book brings together a range of interdisciplinary contributors from across the globe to explore the most pressing issues facing those working in and with philanthropy and education. It focuses on the increasing influence of new philanthropic actors on the global education sector, offering a thorough insight into the topic. This engaging book explores actor relationships in philanthropic and educational spaces, and examines different types of philanthropy, including corporate, family and state giving, as well as examining the latest trends in the field. Chapters build on research from the Global North/Global South, offering a wide range of perspectives on philanthropy and education in Africa, South America, North America and the Middle East. New actors, new partnerships and new roles emerging in philanthropic engagement with the education sector are highlighted, offering insight into innovative approaches to finance and the impact of public-private partnerships. Suggesting key areas of discussion for future research, this discerning book is a vital read for development studies, philanthropy and globalisation scholars. It also contains critical analysis of the role of philanthropic organisations working in the education space for policy-makers looking to understand the field in more depth.